Dumbarton Oaks. Byzantine Studies <http://www.doaks.org/Byzantine.html> - Cilento, Adele (Reti Medievali Rivista, 2002)
Recensione a Dumbarton Oaks. Byzantine Studies <http://www.doaks.org/Byzantine.html>